Pilihan Rasional Perempuan Menikah Di Usia Dini (Studi Kasus Di Desa Mamben Daya, Kecamatan Wanasaba, Kabupaten Lombok Timur) - Ropida, Ropida; Kebayantini, Ni Luh Nyoman; Ranteallo, Ikma Citra (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRAK Under age marriage in north Mamben Daya Village, subdistrict of Wanasaba, East Lombok regency mostly afficted to the women if it comparedwith te man. The age of women who get merried at under age was about 10 to 15 year old. Under age marriage is not always become a problem so that from years to years amount of the under age marriage women is increase significantly.Statement problem of this study are (1) Why do the women chose to get merried at young age? (2) How the under age marriage cab effect to the family life?Study approach of this research is qualitative research has done in north Mamben Daya Village. This is a study case while the type of this research is descriptive method. Purprose of this study is to describe the reason of the women who get merried at under age and the effect of under age marriage. Theoritical frameworkthat used in this study was rasional choise of James Coleman.The result of this study shows that the women who get married at under age indirectly mostly caused by financial reason in her family life beside that merariq tradition andÂ dedare tuaq symbol legitimate the caused of under age marriage to the women furthermore there are some things that the women has to sacrifie in under age marriage (1) education, (2) adolescene, (3) boyfriend. Under age marriage has positive and negative effect, for the parents of the womenÂ it has positive effect. They can decrease financial responsibility and avoid symbol of dedare tuaq for their daughter. Meanwhile negative effect of under age marriage for the women mostly get domestic andvioleace then divorce lastly and effect to the pregnance and to the baby that willÂ abnormally. Keywords: women, rational choice, under age marriage.